NUMERICAL SIMULATION OF THE THERMAL PROCESS IN THE PERFORATED GRAPHITE SHEET BY MESHLESS METHOD - Protektor, Denys; Hariachevska, Iryna (Collection of scientific papers «ΛΌГOΣ», 2023)
This paper presents the numerical simulation results of the thermal process in a perforated graphite sheet obtained by meshless method for solving three-dimensional non-stationary heat conduction problems in anisotropic solids [1, 2].